Malaysia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the extent to which the Malaysian economy has been hit by a number of external and domestic shocks since late 2014, including sharply lower energy prices, spillovers from China, capital outflows, and domestic political controversies. The 2016 budget, including January recalibration, reaffirms the government's commitment to fiscal consolidation. The current accommodative monetary policy stance is appropriate in an environment of moderating growth and low inflation. Facing sizeable capital outflows and a sharp fall in oil and commodity prices, exchange rate depreciated substantially. The central bank deployed reserves; the effect on domestic interest rates was modest. Credit growth has moderated, a welcome development after several years of double-digit growth.